O acesso aberto à investigação em Ciência da Informação em Portugal : alcance e impacto - Ribeiro, Fernanda (2009)
The main purpose of this paper is to study the open access, its generalization and impact in whatconcerns Information Science, in Portugal. Thus, the repositories that keep works of interest forthe scientific and academic community are analysed, as well as the Portuguese periodicals in thearea of Information Science.In order to analyse the repositories, with special focus in those of Portuguese universities, wereselected several indicators, which enable to have a general vision of their way of functioning,evolution and effects. These indicators refer to the software used in the creation of therepository, its dimension, the authors involved, the typology of the documents and thosenetworks to which they belong, as nationally, as internationally.Once the overview of the repositories is done, an exploratory study is taken on in order to knowthe impact of the open access in Information Science, taking as a basis of analysis theperiodicals, the universities' repositories that integrate RCAAP and the specialized repositoryE-LIS. The results reflect a quite incipient situation, either in what concerns to the participationof publishers in the open access movement, or the use of the repositories and the self-archive. Itis not possible yet to establish a direct and positive correspondence between open access andresearch impact.